The slit lamp : Applications for biomicroscopy and videography - Gellrich, Marcus-Matthias (Springer Berlin Heidelberg, 2014)
In this book the author describes in detail the history, construction, and examination potential of the slit lamp. In particular, however, he presents a new approach - videography - that allows the ophthalmologist to document all (!) eye diseases with the slit lamp and a video camera in a practicable, rapid, and affordable manner. The necessary methods, techniques, and equipment, including converging, diverging, and contact lenses, are clearly explained in the text and four didactic videos. The 20 most important videographic settings are described, and "recipes" for their use are presented, along with diagnostic tips. The accompanying collection of clinical images represents the world's first ever general atlas of ophthalmology from the perspective of the slit lamp. The author has already demonstrated proof of the value of ophthalmological videography in his own practice. It is his hope that this introductory book, with its many images never previously produced with a slit lamp, will stimulate others to exploit the approach's potential.